2022
DOI: 10.1002/slct.202202234
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Silver Nanoparticles Loaded Biomimetic Isomeric Short Lipopeptide Nanostructures

Abstract: Lipopeptide‐inspired lipidation of two short tripeptides, Phe‐Tyr‐β‐Ala and Tyr‐Phe‐β‐Ala leads to a pair of constitutional isomers of short peptide amphiphile (sPA). These two molecules were able to mimic lipopeptides properties and therefore could be used as potential drug delivery vehicles up to target sites. Further, these isomeric peptide amphiphiles were able to synthesize stable silver nanoparticles (AgNPs) in presence of sunlight without using any reducing agents. Interestingly, the presence of AgNPs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…Therefore a new strategy for predicting the degree of stability of sPA structures was used by studying its secondary structural properties. Three variants of short peptide amphiphiles were further synthesized by the insertion of a tyrosine residue at the appropriate position [16] . It is otherwise stated that the selective hydroxylation (Tyr‐insertion) of Phe1 and Phe2 moiety in sPA lead to sPA2 and sPA3 respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore a new strategy for predicting the degree of stability of sPA structures was used by studying its secondary structural properties. Three variants of short peptide amphiphiles were further synthesized by the insertion of a tyrosine residue at the appropriate position [16] . It is otherwise stated that the selective hydroxylation (Tyr‐insertion) of Phe1 and Phe2 moiety in sPA lead to sPA2 and sPA3 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is otherwise stated that the selective hydroxylation (Tyr‐insertion) of Phe1 and Phe2 moiety in sPA lead to sPA2 and sPA3 respectively. Studies have shown that all three hydroxylated (sPA2 and sPA3) and their non‐hydroxylated (sPA) sPAs have high biocompatibility with the bacterial cell membrane [17,18] and the potential to synthesize Ag/AuNPs, therefore, were used to develop antibacterial materials [13,16,19] . Accordingly given our emerging interest, this time too we have developed a new variant of sPA by replacing both Phe1 and Phe2 with Tyr (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations